Extensive Bilateral Extraluminal Perivascular Pulmonary Haemorrhage Associated with Stanford Type A Aortic Dissection. (11th August 2011) - Reid, Angeline; Stride, Peter; Hunter, Jonathan; Liew, Katerina; Wood, T.; Seleem, Mostafa
Abstract : We present the case of an 80-year old man with a Stanford Type A dissecting thoracic aortic aneurysm plus the unusual CT finding of extramural haemorrhage along the pulmonary vessels. The clinical and radiological picture has an extremely high mortality